Nanowires Fundamental Research - Hashim, Abbass (IntechOpen, 2011)
Understanding and building up the foundation of nanowire concept is a high requirement and a bridge to new technologies. Any attempt in such direction is considered as one step forward in the challenge of advanced nanotechnology. In the last few years, InTech scientific publisher has been taking the initiative of helping worldwide scientists to share and improve the methods and the nanowire technology. This book is one of InTech's attempts to contribute to the promotion of this technology.